Flawed citation practices facilitate the unsubstantiated perception of a global trend toward increased jellyfish blooms. Issue 9 (22nd June 2016) - Sanz‐Martín, Marina; Pitt, Kylie A.; Condon, Robert H.; Lucas, Cathy H.; Novaes de Santana, Charles; Duarte, Carlos M.
Abstract: Speculation over a global rise in jellyfish populations has become widespread in the scientific literature, but until recently the purported 'global increase' had not been tested. Here we present a citation analysis of peer‐reviewed literature to track the evolution of the current perception of increases in jellyfish and identify key papers involved in its establishment. Trend statements and citation threads were reviewed and arranged in a citation network. Trend statements were assessed according their degree of affirmation and spatial scale, and the appropriateness of the citations used to support statements was assessed. Analyses showed that 48.9% of publications misinterpreted the conclusions of cited sources, with a bias towards claiming jellyfish populations are increasing, with a single review having the most influence on the network. Collectively, these disparities resulted in a network based on unsubstantiated statements and citation threads. As a community, we must ensure our statements about scientific findings in general are accurately substantiated and carefully communicated such that incorrect perceptions, as in the case of jellyfish blooms, do not develop in the absence of rigorous testing.